Online Learning: Signal Integration and Augmented Reality Helping Children with Down Syndrome - Nor Azril Mohd Ghazali; Che Zalina Zulkifli; Mohd Zahuri Khairani; Mohd Fauzi Sedon; Joko Suyono; Yohanes Sugiyanta (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: This study focuses on how online learning can aid in the development of the Augmented Reality (AR) technology,